Venture Capitalist Certification in Initial Public Offerings. - Megginson, William L; Weiss, Kathleen A (Journal of Finance, 1991)
This paper provides support for the certification role of venture capitalists in initial public offerings (IPOs). Consistent with the certification hypothesis, a comparison of venture capital backed IPOs with a control sample of nonventure capital backed IPOs from the 1983 through 1987 matched as closely as possible by industry and offering size indicates that venture capital backing results in significantly lower initial returns and gross spreads. In effect, the presence of venture capitalist in the issuing firms serves to lower the total costs of going public and to maximize the net proceeds to the offering firm. In addition, the authors document that venture capitalists retain a significant portion of their holdings in the firm after the IPOs.